Peran Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan - Dewi, Dewa Ayu Putu Aprilia Citra; Susila, Gede Putu Agus Jana (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study was conducted to examine the effect ofcompensation and work motivation on employee performance at PT Indah Permai Cabang Singaraja. This research is a quantitative research. Data collection was carried out by questionnaire and interview methods. There were 45 respondents participated. Then, the data were analyzed using multiple linear regression analysis methods. The results showed that (1) compensation and work motivation simultaneously had a positive and significant effect on employee performance at PT Indah Permai Cabang Singaraja, (2) compensation had a positive and significant effect on employee performance at PT Indah Permai Cabang Singaraja, and (3) work motivation had a positive effect and significant on employee performance at PT Indah Permai Cabang Singaraja.